Project integration management of the Kliptown Renewal Precinct in Johannesburg - Moodley, Vinesh (My University, 2014)
ABSTRACT Project Integration Management is regarded as one of the key knowledge areas in project management that determines project management success and project success in both private and public sector projects. This report assesses the Kliptown Renewal Precinct project as a public sector project in terms of its level of project integration management in attempting to understand the reasons for the reported delays in the project (JDA, 2012). This project was implemented by the Johannesburg Development Agency (JDA) as a catalytic project to uplift the community by creating employment and business opportunities, stimulating the local economy, developing an efficient transport node and encouraging tourism growth (Wessels, 2006). Similar urban space development programmes are planned for other communities, municipalities and provinces as well as nationally, so the reasons for this delay are important in the context of these future similar projects. The theoretical framework will assess this project in relation to project integration management processes encompassing factors leading to project management success and project success, and how the two are aligned through these project integration processes. Through this analysis, conclusions have been drawn on the application of project integration management processes and how the processes have impacted on the delivery of this public sector project from a project management success perspective and a project success perspective. Recommendations on how to implement the good practices of this project as well as recommendations on how to address the shortcomings from a project management basis are also proposed so as to create a repository of information for future similar projects.
MM Thesis 2014
Keywords: Project management -- South Africa.; Sustainable development -- South Africa -- Johannesburg.; Urban renewal -- South Africa -- Johannesburg.